COVID-19–Related Outcomes in Primary Mitochondrial Diseases: An International Study. (5th April 2022) - Pizzamiglio, Chiara; Machado, Pedro M.; Thomas, Rhys H.; Gorman, Gráinne S.; McFarland, Robert; Hanna, Michael G.; Pitceathly, Robert D. S.; ,
Abstract : Background and Objectives: To identify factors associated with severe coronavirus disease 2019 (COVID-19), defined by hospitalization status, in patients with primary mitochondrial diseases (PMDs), thereby enabling future risk stratification and informed management decisions. Methods: We undertook a cross-sectional, international, registry-based study. Data were extracted from the International Neuromuscular COVID-19 Database and collected between May 1, 2020, and May 31, 2021. The database included subjects with (1) PMD diagnosis (any age), clinically/histopathologically suspected and/or genetically confirmed; and (2) COVID-19 diagnosis classified as "confirmed", "probable", or "suspected" based on World Health Organization definitions. The primary outcome was hospitalization because of COVID-19. We collected demographic information, smoking status, coexisting comorbidities, outcomes after COVID-19 infection, and PMD genotype-phenotype. Baseline status was assessed using the modified Rankin scale (mRS) and the Newcastle Mitochondrial Disease Adult Scale (NMDAS). Results: Seventy-nine subjects with PMDs from 10 countries were included (mean age 41.5 ± 18 years): 25 (32%) were hospitalized, 48 (61%) recovered fully, 28 (35%) improved with sequelae, and 3 (4%) died. Statistically significant differences in hospitalization status were observed in baseline status, including the NMDAS score ( p = 0.003) and mRS ( p = 0.001), presence of respiratory dysfunction ( p < 0.001), neurologic involvement ( p = 0.003), and more than 4 comorbidities ( p = 0.002). In multivariable analysis, respiratory dysfunction was independently associated with COVID-19 hospitalization (odds ratio, 7.66; 95% CI, 2–28; p = 0.002). Discussion: Respiratory dysfunction is an independent risk factor for severe COVID-19 in PMDs while high disease burden and coexisting comorbidities contribute toward COVID-19–related hospitalization. These findings will enable risk stratification and informed management decisions for this vulnerable population.